Approach to the anxiety and coping perceived of mathematics during the pandemic in higher level students in an environment rich in symbols - López-Ramírez, Enrique; Dehesa-De-Gyves, Nahina; García-Jarquín, Brenda; Varapizuela-Sánchez, Carlos Francisco; García-Montalvo, Iván Antonio (Frontiers in Education, 2025)
Although the curricula recognize the attitudinal component as a crucial competence for students to develop, the reality is that the integration of this objective with the extensive conceptual content that must be covered needs to be emphasized even more. If this integration is neglected, it may lead to anxiety during the learning process. In the present study, we conducted semi-structured interviews with students to explore their motivations for studying mathematics and the various strategies they employed to cope during the pandemic. These interviews not only revealed the complexity of this integration but also highlighted a context that could be linked to the specific social environment in which the students are immersed.